Սրբազան արժեքներ՝ մեղեդային շնչով. զրադաշտական տեքստերի երաժշտական ոգին - Մուրադյան, Ալմաստ («Զանգակ - 97»)
Analyzing a number of evidences of Zoroastrian melodies, the earliest manifestations of Iranian ancient culture and especially music, we can state that we are talking about ancient sources in Persian music, which were created under the influence of religious prayers and became an integral part of the culture. Zoroastrian traditions, including traditions of musical and poetic art, were preserved or transformed under the conditions of the common Indo-Iranian cultural complex. And the Zoroastrian musical tradition was interconnected with the social structure of the society and the changes in it. The holy book of religion, Avesta is not only a religious, cultural, legal source, but also a source, the texts of which became the basis for new religious songs. These works were performed during religious rituals and were originally the monopoly of the priests. As in religion, so in Zoroastrian melodies, the themes relate to justice and light and have reached the present day. The most prominent of the melodies are based on the famous "Mantras" from the Gathas, performed to the accompaniment of various instruments, of which the role of the trumpet, an instrument used by the semi-mythical Yima, is symbolic. Some researchers conclude that even thanks to the Avesta, a special musical language was formed, its intonation features were updated and enriched. And the tradition of singing the sacred texts of the Avesta stimulated the development of vocals and the entire musical culture, which flourished during the Achaemenid dynasty, when musicians were considered representatives of a worthy class, and it continued under the Sassanids, reaching its peak. Musicians working in the Persian court continued the rich musical traditions. We referred to the activities of Barbad Mervezi, a famous musician, poet, nightingale of Iran, who had a series of songs for the days of the Zoroastrian calendar. And one of the recent researches shows that the most famous Zoroastrian singer, the prophet Zarathustra, sang hymns from the Avesta using 4 different musical methods. Zoroastrian music survived until the Middle Ages, and Nizam's mentions of the presence of Zoroastrian melodies in the repertoire of court musicians are a vivid evidence.
Keywords: Երաժշտական-ազգագրական ժառանգություն